Radicular Pain Syndromes: Cervical, Lumbar, and Spinal Stenosis - Patel, Ekta A.; Perloff, Michael D. (Seminars in Neurology, 2018)
Back pain is a top primary and urgent care complaint; radicular pain can be caused by herniation of the nucleus pulposus (intervertebral disc), spinal stenosis, or degenerative changes to the vertebrae. The focus of this clinical review will be the clinical approach and treatment of lumbar radicular pain, cervical radicular pain, and spinal stenosis. Usually localized through neurological history, exam, and imaging, specific signs and symptoms for lumbar radicular, spinal stenosis, and cervical radicular pain can help determine etiology. Once radicular back pain has been diagnosed, a multitude of treatment options are available from rest and physical therapy to medications, epidurals, and surgery. The most common and accepted are reviewed. With accurate diagnosis, safe and effective pain management can be employed to shorten radicular episodes and manage recurrent or chronic radicular syndromes. Using a step-wise approach from diagnosis to conservative therapy to potential surgery, radicular pain syndromes can improve or resolve, and patients may achieve a better functional status and quality of life.
Keywords: Radicular Pain; sciatica; spinal stenosis; lumbar radiculitis